Developing Metacognitive Skills: A Potential Intervention for Employability Enhancement - Nimmi, M P; A, Zakkariya K (Journal of Contemporary Research in Management (JCRM), 2017)
Metacognition-the process of thinking about thinking- a determinant of Employability need to gain the attention of researchers as a major tool for employability intervention. The paper tries to capture the elements of metacognition and its relevance in learning, teaching and training. The different developmental stages of metacognition are examined to see in which age group the metacognitive ability is most prominent. The latter half of the article tries to encompass the denotation of Employability and its importance in present scenario. The theoretical constructs on which the concept is developed is analysed and the various models of Employability are looked into. The Employability model (USEM model) with metacognition as important variable is discussed. Later the research gap existing in current literature pertaining to metacognition as an element of Employability is enlisted. Future research initiatives and practical implications of the same are discussed at the end of paper.